Trust when financial implications are not the aim: the integration of sustainability into management education - Delgado-Márquez, Blanca L.; Aragón-Correa, J. Alberto; Cordón-Pozo, Eulogio; Pedauga, Luis Enrique (Journal of Business Economics and Management, 2016)
Literature has paid detailed attention to the positive financial implications of considering the stakeholders’ environmental concerns. This paper contributes by using a trust framework to delimitate how stakeholders may influence managers’ environmental decisions even if they are not focused on financial objectives. Specifically, we analyse how perceptions of academic department heads about their stakeholders’ ability and benevolence influence the head’s willingness to integrate sustainability issues into the syllabus of the courses. We also investigate the direct and moderating role of the heads’ interest in financial aims and the direct influence of the school environmental proactivity. Our analysis includes a sample of 74 deans in 46 different business and engineering schools and a sample of 95 department heads in the field of management studies of 25 Spanish universities. The hierarchical moderated regression results confirm the positive influence of the ability and benevolence of the stakeholders and the heads’ interest in the financial aims, but not the moderating effects and the influence of the school proactivity. The paper provides research implications on the stakeholders’ dimensions influencing environmental decisions and practical implications showing that managers of organisations who wish to advance their environmental approaches may use partnerships with their stakeholders based upon trust.